2022
DOI: 10.12659/ajcr.935473
|View full text |Cite
|
Sign up to set email alerts
|

Portal and Mesenteric Vein Thrombosis Associated with Decompression Sickness in a 48-Year-Old Deep Sea Self-Contained Underwater Breathing Apparatus (SCUBA) Diver

Abstract: Patient: Male, 48-year-old Final Diagnosis: Mesenteric vein thrombosis • portal vein thrombosis Symptoms: Abdominal pain • nausea Medication: — Clinical Procedure: — Specialty: Gastroenterology and Hepatology • Hematology • General and Internal Medicine • Sports Medicine Objective: Unusual clinical course Background: Deep sea diving can cause decompression illness which comprises both decompression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Eventually, PVT has been related to sports injuries. Dumic et al reported a case of PVT secondary to abdominal trauma related to the practice of brazilian jiu-jitsu in a 32-year-old man with no other traditional risk factors for PVT [ 71 ]; other cases have been described as correlated with decompression sickness in a 48-year-old deep sea self-contained underwater breathing apparatus (SCUBA) diver [ 72 ] and with kickboxing [ 73 ].…”
Section: Risk Factors For Portal Vein Thrombosismentioning
confidence: 99%
“…Eventually, PVT has been related to sports injuries. Dumic et al reported a case of PVT secondary to abdominal trauma related to the practice of brazilian jiu-jitsu in a 32-year-old man with no other traditional risk factors for PVT [ 71 ]; other cases have been described as correlated with decompression sickness in a 48-year-old deep sea self-contained underwater breathing apparatus (SCUBA) diver [ 72 ] and with kickboxing [ 73 ].…”
Section: Risk Factors For Portal Vein Thrombosismentioning
confidence: 99%